"Makassar World City": Regional Development Orientation in the Discourse of Populism - Herman, Herman; Aslinda, Aslinda; Adia Purna, Zarni; Didin, Didin; Rizal MI, Syamsul (Iapa Proceedings Conference, 2024)
This research aims to explore and analyze the impact of populist discourse on regional development orientation in Makassar, particularly in the context of efforts to achieve the vision of "Makassar as a World City." Using a phenomenological approach, data were collected through semi-structured interviews with various stakeholders, text analysis of regional planning documents, and field observations. The results of the study indicate that populist policies often emphasize short-term gains, such as rapid infrastructure development and social welfare programs. However, they face long-term sustainability challenges, unequal distribution of benefits, and a lack of transparency in the use of public funds.